LIVE STREAMING FOR YOUR LIFE: HOW THE DAGO ELOS COMMUNITY USES INSTAGRAM TO BROADCAST THEIR PROTEST FOR LAND RIGHTS - Efendi, Muklis; Pratiwi, Aprilianti; Muqsith, Munadhil Abdul; Ayuningtyas, Fitria; Waluyo, Lukman Saleh (ASPIKOM Jabodetabek Region, 2025)
Urban land conflicts are still a complex and complicated issue in Indonesia. One of the phenomenal urban land conflicts in Indonesia is the conflict between the residents of Dago Elos, Bandung and the Muller Family and PT Dago Intigraha. The conflict began with a claim made by the Muller brothers in 2016 to a 6.3-hectare piece of land that has long been inhabited by hundreds of residents. The purpose of this study is to analyze the use of Instagram Live as a new alternative media in the resistance of Dago Elos residents in Bandung, West Java. The concept used is alternative media. The method in this study is qualitative with digital observation data collection techniques with thematic analysis techniques. The results of the study found that Dago Elos residents use the live streaming feature on Instagram as a medium to voice dissatisfaction and fight for justice by Dago Elos residents. The live streaming is presented not only documenting the repressive actions of the authorities, but also creating a space for citizens to express their collective identity and challenge the dominant narrative. However, there are challenges in using this live streaming in the act of resistance, namely the lack of interaction in the comment column. Through this research, it can be recommended the need to socialize before taking action, namely by disseminating information about the action plan through social media platforms, community groups and the WhatssApp application.